Identification and Characterization of GPCRs for Pyrokinin and CAPA Peptides in the Brown Marmorated Stink Bug, Halyomorpha halys (Hemiptera: Pentatomidae) - Ahn, Seung-Joon; Corcoran, Jacob A.; Vander Meer, Robert K.; Choi, Man-yeon (Frontiers in Physiology, 2020)
The brown marmorated stink bug, Halyomorpha halys, is an invasive hemipteran that causes significant economic losses to various agricultural products around the world. Recently, the pyrokinin and capa genes that express multiple neuropeptides were described in this species. Here we report six pyrokinin and capa GPCRs including two splice variants, and evaluate their a) ability to respond to neuropeptides in cell-based assays, and b) expression levels by RT-PCR. Functional studies revealed that the H. halys pyrokinin receptor-1 (HalhaPK-R1a & b) responded to the pyrokinin 2 (PK2) type peptide. RT-PCR results revealed that these receptors had little or no expression in the tissues tested, including the whole body, central nervous system, midgut, Malpighian tubules, and reproductive organs of males and females, suggesting that HalhaPK-R1 may no longer have a biological function in this organism. HalhaPK-R2 showed the strongest response to PK2 peptides and a moderate response to pyrokinin 1 (PK1) type peptides (=DH, diapause hormone), and was expressed in all tissues tested. HalhaPK-R3a & b responded to both PK1 and PK2 peptides. Their gene expression was restricted mostly to the central nervous system and Malpighian tubules. All PK receptors were dominantly expressed in the fifth nymph. HalhaCAPA-R responded specifically to CAPA-PVK peptides (PVK1 and PVK2), and was highly expressed in the Malpighian tubules with low to moderate expression in other tissues, and life stages. Of the six GPCRs, HalhaPK-R3b showed the strongest response to PK1. Our experiments associated the following peptide ligands to the six GPCRs: HalhaPK-R1a & b and HalhaPK-R2 are activated by PK2 peptides, HalhaPK-R3a & b are activated by PK1 (=DH) peptides, and HalhaCAPA-R is activated by PVK peptides. These results pave the way for investigations into the biological functions of H. halys PK and CAPA peptides, and possible species-specific management of H. halys.